Plasmadiafiltration ameliorating gut mucosal barrier dysfunction and improving survival in porcine sepsis models - Li, Ming Xin (Intensive Care Med Exp, 2016)
BACKGROUND: The object of this study is to explore whether the plasmadiafiltration (PDF) is more effective in improving the intestinal mucosal barrier function by removing more key large molecular inflammatory mediators and then prolonging the survival time. METHODS: Totally, 24 porcine sepsis models induced by cecal ligation and puncture (CLP) operation were randomly divided into three groups: PDF group, high-volume hemofiltration (HVHF) group, and control group, and received 8 h treatment, respectively. The expression of ZO-1 and occludin in intestinal mucosal epithelial cells were detected by immunohistochemistry, and apoptotic protein caspase-3-positive lymphocytes were signed in mesenteric lymph nodes by TUNEL staining. The hemodynamic parameters were measured by invasive cavity detection. The tumor necrosis factor alpha (TNFα) and high-mobility group protein 1 (HMGB1) were tested by ELISA method. And then, the survival curves with all-cause death were compared with three groups. RESULTS: PDF led to a superior reversal of sepsis-related hemodynamic impairment and serum biochemistry abnormalities and resulted in longer survival time compared with HVHF and control (p < 0.01). Definitive protection from excessive TNF-α and HMGB1 response were only achieved by PDF. A more regular distribution pattern of ZO-1 and occludin along the epithelium was found in PDF animals (p < 0.01). The presence of apoptotic lymphocytes was significantly reduced in the PDF animals (p < 0.01). CONCLUSIONS: PDF can effectively eliminate more pivotal inflammatory mediators of TNFα and HMGB1 and reduce the inflammation damage of the intestinal mucosal barrier and apoptosis of lymphocyte then improve the circulation function and prolong the survival time.